Daya Saing Kopi Indonesia di Pasar Internasional - Dita Milih Anggraini; Iwan Aminudin; Acep Muhib (Sharia Agribusiness Journal, 2022)
The scope of this research includes international coffee commodity trading using the Harmonized System (HS) code 0901. The method used in this study uses Herfindahl Index (HI), the Revealed Comparative Advantage (RCA), the Diamond Porter Sistem and the Trade Specialization Index (ISP). Results HS 0901 uses HI known to have a monopolistic market structure with a value of 726.30. RCA method, the four largest coffee exporter countries in Indonesia have values with an average of 3.89. These values mean that Indonesia has a strong comparative advantage but is still below the countries of Brazil, Colombia and Vietnam. Indonesia has strong competitiveness in the main coffee export destination countries with an average RCA value, Morocco (146.49), Georgia (105.99), Egypt (29.65), UK (18.35), Germany (10.95), Italy (8.66), Malaysia (8.29), US (6.32), Singapore (5.26) and Japan (2.05).  Results of the analysis with Diamond Porter Sistem Indonesia has a competitive advantage with strong competitiveness as proven by most of the main components supporting each other. But there are links that are not mutually supportive, namely the condition of resource-bound industries and supporting industries and the conditions of resource-conditions of demand. Based on ISP analysis of the position or stages of the development of Indonesia's coffee trade with a value of 0.90. This value shows the coffee commodity is in the fourth stage or at the maturity stage. Indonesian coffee is already at the stage of standardization on the technology used. This shows Indonesia as a coffee exporter in the international market.Keywords: Coffee, Market Share, Competitive Advantage, Diamond Porter SystemAbstrak:Ruang lingkup penelitian ini meliputi perdagangan komoditas kopi internasional dengan menggunakan kode Harmonized System (HS) 0901. Metode yang digunakan dalam penelitian ini menggunakan Herfindahl Index (HI), Revealed Comparative Advantage (RCA), Diamond Porter System dan Indeks Spesialisasi Perdagangan. (ISP). Hasil analisis HS 0901 menggunakan HI diketahui memiliki struktur pasar monopoli dengan nilai 726,30. Metode RCA, empat negara pengekspor kopi terbesar di Indonesia memiliki nilai dengan rata-rata 3,89. Nilai tersebut berarti Indonesia memiliki keunggulan komparatif yang kuat namun masih di bawah negara-negara Brazil, Kolombia dan Vietnam. Indonesia memiliki daya saing yang kuat di negara tujuan utama ekspor kopi dengan nilai RCA rata-rata, Maroko (146,49), Georgia (105,99), Mesir (29,65), Inggris (18,35), Jerman (10,95), Italia (8,66), Malaysia (8,29). ), AS (6,32), Singapura (5,26) dan Jepang (2,05). Hasil analisis dengan Diamond Porter Sistem Indonesia memiliki keunggulan kompetitif dengan daya saing yang kuat yang dibuktikan dengan sebagian besar komponen utama saling mendukung. Namun ada keterkaitan yang tidak saling mendukung, yaitu kondisi industri yang terikat sumber daya dan industri pendukung dan kondisi sumber daya-kondisi permintaan. Berdasarkan analisis ISP posisi atau tahapan perkembangan perdagangan kopi Indonesia dengan nilai 0,90. Nilai ini menunjukkan komoditas kopi berada pada tahap keempat atau pada tahap kematangan. Kopi Indonesia sudah dalam tahap standardisasi teknologi yang digunakan. Hal ini menunjukkan Indonesia sebagai eksportir kopi di pasar internasional.Kata kunci: Kopi, Pangsa Pasar, Keunggulan Kompetitif, Diamond Porter Sistem.